The association of healthy eating index score and n-3 fatty acid intake with cardiovascular diseases incidence and lipid biomarkers in Alberta’s tomorrow project cohort - Taheri, Reihane; Weaver, Olivia; Ye, Ming; Vena, Jennifer E.; Johnson, Jeffrey A.; Vine, Donna; Eurich, Dean; Proctor, Spencer D. (Frontiers in Nutrition, 2025)
IntroductionUnhealthy diet and dyslipidemia are major risk factors for cardiovascular disease (CVD). Studies have shown an inverse association between greater n-3 fatty acid (FA) intake and reduced dyslipidemia and CVD risk. We aimed to assess the association of the healthy eating index (HEI) score and n-3 FA intake with CVD incidence and non-fasting RC in the Alberta’s Tomorrow Project (ATP) cohort.MethodsThis is a prospective study on a subset of ATP study participants (n = 23,248), with the mean age of 50.2 (35-69) years, 36% male and 64% female, and no history of cancer or CVD in Alberta, Canada. Dietary intake was assessed using the Canadian Diet History Questionnaire (CDHQ), from which the Canadian HEI-2005 score and total n-3 FA intake were calculated. Lipid panel markers were measured from non-fasting blood samples, and CVD was defined using the International Statistical Classification of Diseases and Related Health Problems from linked administrative health records. The Cox proportional hazard model, linear regression, and logistic regression were used to assess the association of dietary intakes with CVD incidence, and lipid biomarkers.ResultsThe mean follow-up was 13.9 years. For every 1 unit increase in the HEI score, the adjusted Hazard Ratio (HR) of developing CVD decreased [HR: 0.98 (95% confidence interval (CI) 0.97–0.98), 0.99 (95%CI 0.98–0.99), and 0.97 (95%CI 0.97–0.98) in females, males, and total cohort, respectively (p < 0.05)]. No significant association was found between absolute n-3 FA intake (g/d) with CVD incidence. However, higher relative intake (i.e., n-3 FA as proportion of energy) increased the risk of developing CVD [HR = 1.42 (95%CI 1.1–1.84), p = 0.006] in males. Adjusted multivariate regression in a subset (n = 8,458) showed no association between n-3 FA (g/d) intake and lipid biomarkers but a significant inverse association between HEI score and non-fasting RC [coefficient: −0.006 (95%CI −0.009–−0.003) for females and −0.01 (95%CI −0.018–−0.005) for males], and TG levels [−0.01 (95%CI −0.015–−0.006) for females and −0.01 (95%CI −0.02–−0.006) for males].DiscussionHigher overall diet quality but not n-3 FA intake was associated with a lower risk of CVD incidence and non-fasting RC.